Supplement Teaching Materials Development Based on PBL with Animal Digestive System Material to Increase Concept Mastery of Junior High School Students - , Indriyati; Isnaeni, Wiwi (FMIPA UNNES, 2022)
Supplementary teaching materials were developed based on the analysis of student needs and observations in learning. Supplements are prepared as supporting teaching materials for teachers to assist in learning activities in the classroom. Researchers made observations on learning resources, the material on the animal digestive system did not contain relevant images, the textual discussion and the examples presented were less varied. One of the learning media that can help overcome these problems is by developing supplementary teaching materials for PBL-based animal digestive system materials to teach junior high school students mastery of concepts. The use of media during the learning process aims so that students can form their own concepts. This study aims to test the eligibility of teaching materials supplements based on validator assessments, test the readability of teaching materials supplements, analyze students' conceptual mastery by looking at improving learning outcomes through the n-gain test and analyze the practicality of teaching materials supplements based on teacher and student responses. This research uses the R&D approach and the ADDIE model. The sample used in this study was class VIII H SMP N 13 Semarang. The results of the assessment of the eligibility of the teaching material supplements were declared very feasible by material and media experts with feasibility scores of 88% and 95% respectively. The readability test of teaching material supplements was stated to be easy to understand with an average score of 82.5%. The n-gain test on the pretest and posttest obtained a result of 0.7 with high criteria. Teacher and students gave a practical or good response after using teaching material supplements as evidenced by an average score of 81% and score teacher response of 89%. Supplements for teaching materials based on PBL for animal digestive system materials that have been developed are effective in supporting learning.